Digital Health Education And Technology Utilization For Midwives and Village Health Cadres: A Multi-Media Approach - Khoirun Nisa; Rian Ardianto; Krisna Widi Nugraha; Arif Setia Sandi A; Anggit Wirasto; Atina Salamah (CV Putra Publisher, 2026)
The utilization of digital technology in health education by community health cadres remains suboptimal due to low digital literacy and reliance on manual systems. This community service program aimed to enhance the capacity of cadres in utilizing digital technology as an effective health education medium. Conducted in Karangrau Village, Banyumas, the activity involved 25 participants, comprising village midwives and community empowerment cadres. The intervention utilized the SMART-CARE Model, integrating a multi-media approach consisting of an interactive educational website, pocket guidebooks, and instructional videos. Evaluation results demonstrated a substantial improvement in participants' understanding, with the average pre-test score increasing from 81% to 97% in the post-test. Furthermore, participants showed enhanced practical skills in accessing and applying digital media for health information delivery, leading to increased technical confidence. In conclusion, the SMART-CARE-based multi-media approach effectively bridged the digital literacy gap and empowered cadres as sustainable community health education agents.